Alcohol Use, Rape Myth Acceptance, Rape Empathy, and Sexual Assault History Influence the Believability of a Hypothetical Victim’s Report of Sexual Assault - Rinehart, Jenny K. (Journal of interpersonal violence, 2023)
College sexual assault is a common problem, and survivors often do not report their experience to college campus officials or law enforcement for fear of not being believed. This study examined how contextual factors such as alcohol use and whether the perpetrator was described as a student-athlete or student, and rater characteristics, such as the history of sexual assault and attitudes toward rape, influenced college students’ perceptions of the believability of a hypothetical victim’s sexual assault account. In all, 449 (N = 449) undergraduates read a vignette describing a hypothetical sexual assault and were assigned randomly to one of four conditions with varying contextual features: college athlete—no alcohol, college athlete—alcohol, college student—no alcohol, or college student—alcohol. They then rated how much they believed the victim in the vignette had been raped (0 [not at all] to 100 [completely]). The presence of alcohol use in the vignette was associated with lower ratings of believability, and participants who were higher in rape myth acceptance and lower in rape empathy rated the hypothetical victim’s rape account as less believable. In addition, women who had been raped previously rated the victim in the vignette as more believable than women with no history of sexual assault. Implications for how college campuses might respond more effectively to reported sexual assaults are discussed.